A Fuzzy Logic-based Tuning Approach of PID Control for Steam Turbines for Solar Applications. (May 2017) - Dettori, S.; Iannino, V.; Colla, V.; Signorini, A.
Abstract: This work aims at improving the control concept based on PID controller by jointly exploiting experience and knowledge on the system behaviour and artificial intelligence. A Concentrated Solar Power Plant (CSPP) system has been modelled and a stability and performance analysis has been carried out, focusing on power control loop, which is normally based on standard PID. A hybrid fuzzy PID approach is proposed to improve the steam turbine governor action and its performance are compared to the classical PID tuned according to three different approaches. Compared to the classic PID, the PID fuzzy logic controller extends the simplicity of PID and adapts the control action at actual operating condition by providing the system with a sort of "decision-making skill". The possibility to design implementable algorithms on PLC, which have stringent computational speed and memory requirements, has been explicitly taken into account in the developed work.